Role of Technological Innovation and Operational Efficiency in Competitive Advantage at Soekarno Hatta International Airport - Charles An; Cecep Pahrudin; Arty Zykra Pratiwi; Syahranny Anzelie Shadewi Naila Syamsuri (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2026)
This research aims to assess the impact of technological innovation and operational efficiency on competitive advantage at Soekarno Hatta International Airport. In the digitalization era, the implementation of technologies such as self check-in services and the Internet of Things (IoT) is crucial for enhancing efficiency and customer satisfaction. Data were collected from 100 airport users using random sampling techniques, with a quantitative analysis conducted through linear regression using SPSS. Validity, reliability, normality, regression, determination (r²), t-test, and f-test were employed in this study. The results of this study show that technological innovation and operational efficiency have a significant impact on competitive advantage, contributing 56.9% to the competitive advantage variable. The combination of technological innovation and operational efficiency plays an important role in enhancing the competitiveness of Soekarno-Hatta International Airport in both domestic and international markets.